1985
DOI: 10.1002/jcp.1041250206
|View full text |Cite
|
Sign up to set email alerts
|

Human spreading factor: Synthesis and response by HepG2 hepatoma cells in culture

Abstract: Human serum spreading factor (SF) is a cell adhesion and spreading-promoting glycoprotein purified from serum or plasma that mediates effects in a wide variety of animal cell culture systems. HepG2 human hepatoma cells were found to synthesize and secrete SF into culture medium. Quantitative immunoassay of the protein indicated a concentration of about 1 microgram/ml in 48 hr-conditioned medium from confluent cultures. Although fibronectin also was synthesized and secreted into the culture medium, HepG2 cell s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…Limited information is available on the tissues that produce Vn in vivo. The liver has been implicated since Vn cDNAs have been isolated from liver cDNA libraries (7,8,22), and two primary hepatocarcinoma cell lines (HepG2 and Hep3B) have been shown to synthesize Vn in vitro (20,23). Moreover, plasma Vn levels are reduced upon liver failure (46).…”
Section: Resultsmentioning
confidence: 99%
“…Limited information is available on the tissues that produce Vn in vivo. The liver has been implicated since Vn cDNAs have been isolated from liver cDNA libraries (7,8,22), and two primary hepatocarcinoma cell lines (HepG2 and Hep3B) have been shown to synthesize Vn in vitro (20,23). Moreover, plasma Vn levels are reduced upon liver failure (46).…”
Section: Resultsmentioning
confidence: 99%
“…It circulates in blood in a monomeric ("closed," "native") form, but is converted into a multimeric ("extended," "opened," "denatured") form when incorporated into the extracellular matrix or treated with urea (1,2). The extended form of VN binds to specific receptors on cells (3,4) and to various other molecules such as the C5b-9 complement complex (5), the thrombin-antithrombin III complex (6,7), plasminogen activator inhibitor 1 (PAI-1) (8 -10), uPAR (11), heparin (1,2,12,13), collagen (14 -16), plasminogen (13,17), and ␤-endorphin (18). These interactions not only promote the attachment, spreading, and growth of cells (19 -21) but also influence the coagulation, fibrinolytic, and complement systems (22,23).…”
Section: Vitronectin (Vn)mentioning
confidence: 99%
“…A number of ligands were identified that interact preferentially with the conformationally altered, denatured form of Vn. These ligands include collagen (11), GAGs (12)(13)(14), ␤-endorphin (15), PAI-1 (16), urokinase receptor-urokinase complex (17), and cells (18). In contrast, thrombin-antithrombin III complexes appear to preferentially interact with native Vn (19), and PAI-1 appears to bind to both forms of Vn (20).…”
mentioning
confidence: 99%